Eriocitrin Disrupts Erythrocyte Membrane Asymmetry through Oxidative Stress and Calcium Signaling and the Activation of Casein Kinase 1α and Rac1 GTPase - Sumiah A. Alghareeb; Jawaher Alsughayyir; Mohammad A. Alfhili (MDPI AG, 2023)
Background: Hemolysis and eryptosis result in the premature elimination of circulating erythrocytes and thus contribute to chemotherapy-related anemia, which is extremely prevalent in cancer patients. Eriocitrin (ERN), a flavanone glycoside in citrus fruits, has shown great promise as an anticancer agent, but the potential toxicity of ERN to human erythrocytes remains unstudied. Methods: Erythrocytes were exposed to anticancer concentrations of ERN (10-100 μM) for 24 h at 37 °C, and hemolysis and associated markers were quantified using colorimetric assays. Eryptosis was assessed by flow cytometric analysis to detect phosphatidylserine (PS) exposure by annexin-V-FITC, intracellular Ca2+ using Fluo4/AM, and oxidative stress with 2-,7-dichlorodihydrofluorescin diacetate (H2DCFDA). ERN was also tested against specific signaling inhibitors and anti-hemolytic agents. Results: ERN caused significant, concentration-dependent hemolysis at 20-100 μM. ERN also significantly increased the percentage of eryptotic cells characterized by Ca2+ elevation and oxidative stress. Furthermore, the hemolytic activity of ERN was significantly ameliorated in the presence of D4476, NSC23766, isosmotic urea and sucrose, and polyethylene glycol 8000 (PEG). In whole blood, ERN significantly elevated MCV and ESR, with no appreciable effects on other peripheral blood cells. Conclusions: ERN promotes premature erythrocyte death through hemolysis and eryptosis characterized by PS externalization, Ca2+ accumulation, membrane blebbing, loss of cellular volume, and oxidative stress. These toxic effects, mediated through casein kinase 1α and Rac1 GTPase, can be ameliorated by urea, sucrose, and PEG. Altogether, these novel findings are relevant to the further development of ERN as an anticancer therapeutic.